An open-label, in-use study assessing the warming sensation accompanying IFF Flavour 316282 and the acceptability and local tolerability of a syrup containing paracetamol and pseudoephedrine for the short-term treatment of symptoms of an upper respiratory tract infection. (16th March 2015) - Furcha, Rowland; Monnet, Joëlle
Objective: The primary objective was to assess the warming sensation caused by IFF Flavour 316282 in a syrup used for short-term treatment by patients suffering from nasal congestion and mild to moderate body pain, headache, fever or sore throat associated with an upper respiratory tract infection. Methods: A single cohort, single treatment arm, open-label study. Subjects received one 30 mL dose of syrup containing IFF Flavour 316282, paracetamol and pseudoephedrine and recorded onset and disappearance of any warming sensation in the mouth/throat. Subjects' assessments of strength and appeal of the sensation, taste, texture and acceptability of the product was investigated using questionnaires. Results: A total of 56 subjects were included; 53 (94.6%) experienced a warming sensation. The median duration of the warming sensation was 114 s (95% confidence interval: 87–120 s). All subjects rated the syrup as excellent, good or fair for treating their symptoms; 100% and 94.6% of subjects respectively described texture and taste as excellent, good or fair. There were no safety concerns, and the syrup was well tolerated. Most subjects liked the warming sensation. Conclusions: IFF Flavour 316282 in a syrup for treatment of upper respiratory tract infection symptoms is associated with a warming sensation. The syrup is well tolerated, safe and palatable.